Correlation of types of diabetic retinopathy and its psychosocial impact - Jani, Chinmay T.; Desai, Tejas H.; Parikh, Sonal; Shah, Ashka S. (International Journal of Research in Medical Sciences, 2018)
Background: Diabetic retinopathy affects majority (70% to 90%) of diabetic patients, causes visual impairment which leads to severe psycho-social disruption in life. Our objective was to study the patients of diabetic retinopathy, co-relate between the types of diabetic retinopathy and the extent of psychosocial impairment in these patients. Methods: Data of the diabetic patients attending the Retina Clinic of C.H. Nagri Eye Hospital, Ahmedabad was collected using a pretested questionnaire. It included ocular history, history related to diabetes, data of ocular examination and type of retinopathy (if present). For psycho-social assessment, the patients were asked to fill the validated Gujarati language version of “General Health Questionnaire -28 (GHQ 28).” Selfscoring was done ranging from 0-1-2-3 (lower to higher disability respectively). Analysis of significance was carried out by Mann-Whitney Test using statistical software. Results: Total 308 patients were studied. The subjects were divided into 3 groups: (A) Diabetes mellitus type-2 (DM-2) patients without retinopathy. (B) DM-2 patients having non-proliferative retinopathy (C) DM-2 patients having proliferative retinopathy. According to the accepted scoring pattern of GHQ-28 (cut of point 25), it was observed that 80.26% of patients having non-proliferative retinopathy in both eyes and 93.75% patients having proliferative retinopathy in both eyes were psychosocially impaired. The impairment was found to be more severe in proliferative retinopathy patients as compared to non-proliferative retinopathy patients. (p value <0.005) (mean GHQ score in PDR=41.88 >NPDR = 35.74). It was also found that in DM-2 patients without retinopathy the average mean score was 25.22 which showed less impairment (p value <0.005). Conclusions: Patients of Diabetic Retinopathy had more psychosocial impairment which shows its significant impact on quality of life and overall health. Psychiatric counselling must be given to the impaired patients to decrease the impact of the disease on the psychosocial aspect of health. It is necessary to decrease the psychosocial suffering along with the control of disease.